Systematic analysis of genomic organization and structure of long non‐coding RNAs in the human genome. Issue 7 (27th February 2013) - Sun, Jie; Zhou, Meng; Mao, Zhi-Tao; Hao, Da-Peng; Wang, Zhen-zhen; Li, Chuan-Xing
Abstract : The genomic architecture of several functional elements in animals and plants, such as microRNAs and tRNA, has been better characterized. As yet, there is very little known about genomic organization and structure of lncRNA in animals and plants. Here, we conducted a genome‐wide systematic computational analysis of genomic architecture of lncRNAs, and further provided a more comprehensive comparative view of genomic organization between lncRNAs and several other functional elements in the human genome. Our study not only provides comprehensive knowledge for further studies into the correlations between the genomic architecture of lncRNAs and their important functional roles in diverse cellular processes and in disease, but also will be valuable for understanding the origin and evolution of lncRNAs. Abstract : ► lncRNAs have a lower propensity to cluster compared with other four types of RNA. ► lncRNAs have a higher incidence rate in fragile regions. ► A large number of lncRNAs are associated with different types of repetitive elements. ► Genomic segmental duplication events also promote the expansion of lncRNA family.